Canaanite religion according to the liturgical texts of Ugarit - Olmo Lete, Gregorio del (Alter Orient und Altes Testament, 2014)
"The present work collects, completes and combines into one organic synthesis a series of earlier studies written since 1986 on the principal texts concerning Ugaritic religious practice and published in Spanish with the title La Religión Cananea (1992). To these we added in the first English edition (1999, rep. 2004) the analysis of an equal number of texts not studied by us before. These texts belong, chiefly, to the practice of magic, which we define as para-religious. In this second English language edition, new texts published later have also been included and a thorough discussion of newly voiced opinions along with the updating of the bibliography and a more accurate transcription of the texts have been carried out"--